COGNITIVE BEHAVIORAL THERAPY PRACTICES FOR DEPRESSION - Kumari Ragini (International Journal of Multidisciplinary Research and Studies, 2021)
CBT is an abbreviation for cognitive-behavioral therapy, which is a term that is used to describe a group of therapeutic approaches that are united by the fundamental concept that mental diseases and psychological suffering are sustained by cognitive variables. This concept is also referred to as the cognitive-behavioral theory. This therapeutic method, which was pioneered by Beck (1970) and Ellis (1962), is based on the central idea that maladaptive cognitions lead to the persistence of emotional discomfort and behavioural disorders. Beck (1970) and Ellis (1962) both contributed to the development of this therapeutic method. According to Beck's paradigm, these maladaptive cognitions are comprised of overarching concepts about the world, the self, and the future.